Selection and Validation of Reference Genes for Quantitative Real-Time PCR Normalization Under Ethanol Stress Conditions in Oenococcus oeni SD-2a - Peng, Shuai; Liu, Longxiang; Zhao, Hongyu; Wang, Hua; Li, Hua (Frontiers in Microbiology, 2018)
The powerful Quantitative real-time PCR (RT-qPCR) was widely used to assess gene expression levels, which requires the optimal reference genes used for normalization. Oenococcus oeni (O. oeni), as the one of most important microorganisms in wine industry and the most resistant lactic acid bacteria (LAB) species to ethanol, has not been investigated regarding the selection of stable reference genes for RT-qPCR normalization under ethanol stress conditions. In this study, nine candidate reference genes (proC, dnaG, rpoA, ldhD, ddlA, rrs, gyrA, gyrB and dpoIII) were analyzed to determine the most stable reference genes for RT-qPCR in O. oeni SD-2a under different ethanol stress conditions (8%, 12% and 16% (v/v) ethanol). The transcript stabilities of these genes were evaluated using the algorithms geNorm, NormFinder and BestKeeper. The results showed that dnaG and dpoIII were selected as the best reference genes across all experimental ethanol conditions. Considering single stress experimental modes, dpoIII and dnaG would be suitable to normalize expression level for 8% ethanol shock treatment, while the combination of gyrA, gyrB and rrs would be suitable for 12% ethanol shock treatment. proC and gyrB revealed the most stable expression in 16% ethanol shock treatment. This study selected and validated for the first time the reference genes for RT-qPCR normalization in O.oeni SD-2a under ethanol stress conditions.